2017
DOI: 10.3390/en10010061
|View full text |Cite
|
Sign up to set email alerts
|

Ion Migration in the Process of Water Freezing under Alternating Electric Field and Its Impact on Insulator Flashover

Abstract: Abstract:Ice flashover threatens the security and reliability of power transmission. However, the ice flashover mechanism of insulators remains poorly understood. This study analyses water droplet freezing and ion distribution in ice layer under alternating electric field. It also investigates ion migration during icing process of insulator string under alternating electric field and its effects on insulator flashover. Results showed that the average freezing time of water droplets was related to electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As shown in the figure, with the increasing of rain intensity, the flashover voltage decreases less than 10%. According to the studies in [18,19], the influence of the water conductivity can be summarized as follows: firstly, a higher conductivity can enhance the local field at the head of the avalanche; secondly, the electrons at the head of the avalanche at the positive side of the drop are faster absorbed by the drop surface and are therefore less efficient in producing photons for secondary avalanches that could enhance the space charge of the aborted streamer.…”
Section: Effects Of Rain Intensitymentioning
confidence: 99%
“…As shown in the figure, with the increasing of rain intensity, the flashover voltage decreases less than 10%. According to the studies in [18,19], the influence of the water conductivity can be summarized as follows: firstly, a higher conductivity can enhance the local field at the head of the avalanche; secondly, the electrons at the head of the avalanche at the positive side of the drop are faster absorbed by the drop surface and are therefore less efficient in producing photons for secondary avalanches that could enhance the space charge of the aborted streamer.…”
Section: Effects Of Rain Intensitymentioning
confidence: 99%
“…m is the characteristic exponent, indicating the effect of ice thickness on the arc flashover gradient. Similarly, the relationship between the arc flashover gradient of the snow-covered insulators and snow thickness can also be expressed by Equation (5). The results in Table 6 are fitted by using Equation (5).…”
Section: Effect Of D On E Lmentioning
confidence: 99%
“…Similarly, the relationship between the arc flashover gradient of the snow-covered insulators and snow thickness can also be expressed by Equation (5). The results in Table 6 are fitted by using Equation (5). The values of A d , m and R 2 are shown in Table 7.…”
Section: Effect Of D On E Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous research has focused on the flashover properties of ice-covered insulators [13][14][15]. Few studies have reported the icing mechanism of insulators.…”
Section: Introductionmentioning
confidence: 99%